Chemical Composition of Major Cassava Varieties in Uganda, Targeted for Industrialisation - Manano, John; Ogwok, Patrick; Byarugaba-Bazirake, George William (Journal of Food Research, 2017)
Uganda is one of the major cassava producing countries in the world. Currently, utilization of cassava is limited to semi-processed products through the informal sector. Cassava has technological potential as a raw material for agro-industrial products, such as flours for baked products, animal feeds and starch. The aim of this study was to investigate the chemical composition of five major cassava varieties grown in Nebbi distict (Uganda), to assess their potential as industrial raw materials. Analysis of the chemical composition of local (Nyamatia and Nyarukeca) and improved (NASE 3, NASE 14, and NASE 19) cassava varieties was carried out using standard methods. Results showed significant (p < 0.05) differences between the varieties indicating high levels of starch, calcium, magnesium, cyanonenic glucosides and phytates. The cassava varieties contain low levels of protein, lipids and minerals with respect to recommended daily intake of these nutrients. Moisture contents ranged from 5.43 for Nyamatia to 10.87 for NASE 19; ash from 1.05 for Nyamatia to 2.39 for NASE 14; crude fiber from 1.06 for Nyamatia to 1.18 for NASE 19; crude protein from 0.74 for Nyarukeca to 1.51 for NASE 14; crude lipid from 0.39 for Nyamatia to 0.63 for NASE 19; and starch contents from 66.72 for NASE 19 to 84.42 for NASE 3. The mineral contents (mg/kg): calcium ranged from 13.15 for Nyamatia to 16.56 for NASE 3; iron ranged from 0.002 for Nyarukeca to 0.01 for NASE 19; zinc ranged from 0.56 for Nyamatia to 0.87 for NASE 3; magnesium ranged from 3.58 for NASE 19 to 3.88 for Nyarukeca; and copper ranged from 0.002 for Nyamatia to 0.14 for NASE 3. The contents of anti-nutrients (mg/kg): cyanogenic glucosides ranged from 30 in NASE 3 and NASE 19 to 800 in Nyamatia; phytates ranged from 661.33 in Nyarukeca to 984.64 in NASE 3; oxalates ranged from 90.6 in Nyarukeca to 227.8 in NASE 3; and tannin ranged from 0.18 in Nyarukeca to 0.33 in NASE 3. Based on the chemical composition results, all the cassava varieties studied contain higher levels of cyanogenic glucosides than recommended by Ugandan and East African Standards, making them unsafe for direct utilization as food and food raw materials for industries at levels beyond 30% in food formulations. The high starch levels in all the cassava varieties make them valuable raw materials for starch and starch-related industries.
Keywords: anti-nutrients, cassava varieties, chemical composition, Uganda